INTEGRASI SUPPLY CHAIN DAN DAMPAKNYA TERHADAP PERFORMA PERUSAHAAN: SURVEI PADA PERUSAHAAN PENYEDIA JASA MAKANAN DI SURAKARTA - Setiawan, Ahmad Ikhwan; Suhardi, Bambang (Benefit, 2005)
This research is aimed to respond that competition in industries is not only the emulationamong company but absolutely supply chain. It is expected to give some benefits information forsome companies to decide the most effective integration method to serve the suppliers andcustomers. By having the best approach of the supplier and customer facing, the company isexpected to be more competitive and to have better performance and competence. This study isdesigned deeply to describe the patterns of the supply chain integration (direction and degree) onthe company and to know the influence of the implementation of the supply chain integration onthe company performance. The population of this research is taken from the services industries inSurakarta by a purposive sampling. The data will be analyzed with descriptive analysis andMann-Whitney test. They are found that the companies have tree major supply chain integrationpatterns such as inward, consumer and periphery facing. The result also shows the significanteffect of supply chain integration on the company performance